2014
DOI: 10.1098/rsif.2014.0106
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of refractive index of condensed reflectin in squid iridocytes

Abstract: Loliginid squid dynamically tune the structural iridescence of cells in their skin for active camouflage and communication. Bragg reflectors in these cells consist of membrane-bound lamellae periodically alternating with low refractive index extracellular spaces; neuronal signalling induces condensation of the reflectin proteins that fill the lamellae, consequently triggering the expulsion of water. This causes an increase in refractive index within the lamellae, activating reflectance, with the change in lame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…We hypothesized that the reflectins are therefore in a state of Coulombic repulsion in the non-reflective state, with phosphorylation overcoming this repulsion, allowing the reflectins to condense and assemble. This explanation is consistent with the electron micrographic images first obtained by Hanlon and coworkers (12), showing that ACh activation of reflectance proceeds with condensation of the intralamellar proteins and subsequent shrinkage of the Bragg lamellae and confirmed by our subsequent microspectrophotometric analyses showing that the refractive index inside the reflectin-containing Bragg lamellae increases progressively, therefore activating and progressively increasing the intensity of reflectance at each of the membrane-bound interfaces with the extralamellar spaces (13,14). …”
supporting
confidence: 77%
“…We hypothesized that the reflectins are therefore in a state of Coulombic repulsion in the non-reflective state, with phosphorylation overcoming this repulsion, allowing the reflectins to condense and assemble. This explanation is consistent with the electron micrographic images first obtained by Hanlon and coworkers (12), showing that ACh activation of reflectance proceeds with condensation of the intralamellar proteins and subsequent shrinkage of the Bragg lamellae and confirmed by our subsequent microspectrophotometric analyses showing that the refractive index inside the reflectin-containing Bragg lamellae increases progressively, therefore activating and progressively increasing the intensity of reflectance at each of the membrane-bound interfaces with the extralamellar spaces (13,14). …”
supporting
confidence: 77%
“…Reflectins assemble within cephalopod cells to form complex condensed nanostructures of high refractive index that produce diverse biophotonic effects [4][5][6][7][8]12,14 . In most cephalopods these structures are static, arising early during cellular development and remaining fixed for the lifetime of the cell 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, upon iridocyte activation initiated by binding of the neurotransmitter acetylcholine (ACh), released from nearby nerve cells, to cell surface muscarinic receptors, a signal transduction cascade culminates in enzymatic phosphorylation of the reflectins, consequently neutralizing their cationic charge and driving assembly of the reflectins to form homogenously densely staining Bragg lamellae 5,7,10 . Measurements demonstrating the reversible efflux of D 2 O and its re-uptake revealed that condensation of the reflectins drives the expulsion of H 2 O from the membrane-bounded lamellae, simultaneously increasing the refractive index contrast between the intracellular and extracellular layers of the Bragg reflector while shrinking their thickness and spacing, thus activating reflectance and progressively tuning the color of the reflected light across the visible spectrum 6,7,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for our DDA calculation, we simulated a single iridocyte by building a grid of one million dipoles into 50 alternating high-index (n ¼ 1.55, densely packed protein) and low-index (n ¼ 1.33, water) layers, each 100 nm thick, with less than 1% variance, within a 5-mm figure S4). The most accurately measured values of the high-refractive index platelets in protein-based iridocytes vary from 1.44 to 1.55 [17][18][19]. We chose the high end of this possible index range due to the extremely densely packed protein platelets we observed in TEM.…”
Section: Discrete Dipole Approximation Of a Single Iridocytementioning
confidence: 99%